2008
DOI: 10.1071/wf07014
|View full text |Cite
|
Sign up to set email alerts
|

Fire activity in Portugal and its relationship to weather and the Canadian Fire Weather Index System

Abstract: The relationships among the weather, the Canadian Fire Weather Index (FWI) System components, the monthly area burned, and the number of fire occurrences from 1980 to 2004 were investigated in 11 Portuguese districts that represent respectively 66% and 61% of the total area burned and number of fires in Portugal. A statistical approach was used to estimate the monthly area burned and the monthly number of fires per district, using meteorological variables and FWI System components as predictors. The approach s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
116
0
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(151 citation statements)
references
References 13 publications
14
116
0
8
Order By: Relevance
“…Fire danger is 'a general term used to express an assessment of both fixed and variable factors of the fire environment that determine the ease of ignition, rate of spread, difficulty of control, and fire impact; often expressed as an index' (FAO 2005 Keetch et al 1968). Of these, we found a very frequent use of FFMC (Cunningham and Martell 1973;Martell et al 1989;Vega-Garcia et al 1995;Wotton et al 2010;Lee et al 2012;Boulanger et al 2014;Li et al 2014;Beccari et al 2015), DC (Wotton et al 2003(Wotton et al , 2010Carvalho et al 2008;Drever et al 2009;Bedia et al 2014) and DMC (Martell et al 1987;Todd and Kourtz 1991;Wotton et al 2003;Magnussen and Taylor 2012), FWI (Haines et al 1983;Martell et al 1987;Vega-Garcia et al 1996;Carvalho et al 2010;Reineking et al 2010;Ager et al 2014;Beccari et al 2015;Papakosta and Straub 2016), ISI (Haines et al 1970(Haines et al , 1983Vega-Garcia et al 1995;Li et al 2014), FFDI (Bradstock et al 2009;Penman et al 2013;Plucinski 2014;Plucinski et al 2014), KBDI (Prestemon and Butry 2005) and ERC (Andrews et al 2003).…”
Section: Predictors For Short-term Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…Fire danger is 'a general term used to express an assessment of both fixed and variable factors of the fire environment that determine the ease of ignition, rate of spread, difficulty of control, and fire impact; often expressed as an index' (FAO 2005 Keetch et al 1968). Of these, we found a very frequent use of FFMC (Cunningham and Martell 1973;Martell et al 1989;Vega-Garcia et al 1995;Wotton et al 2010;Lee et al 2012;Boulanger et al 2014;Li et al 2014;Beccari et al 2015), DC (Wotton et al 2003(Wotton et al , 2010Carvalho et al 2008;Drever et al 2009;Bedia et al 2014) and DMC (Martell et al 1987;Todd and Kourtz 1991;Wotton et al 2003;Magnussen and Taylor 2012), FWI (Haines et al 1983;Martell et al 1987;Vega-Garcia et al 1996;Carvalho et al 2010;Reineking et al 2010;Ager et al 2014;Beccari et al 2015;Papakosta and Straub 2016), ISI (Haines et al 1970(Haines et al , 1983Vega-Garcia et al 1995;Li et al 2014), FFDI (Bradstock et al 2009;Penman et al 2013;Plucinski 2014;Plucinski et al 2014), KBDI (Prestemon and Butry 2005) and ERC (Andrews et al 2003).…”
Section: Predictors For Short-term Studiesmentioning
confidence: 96%
“…Temporal variables drive short-term models. High mean and maximum temperatures (Alonso-Betanzos et al 2003;Preisler et al 2004;Carvalho et al 2008Carvalho et al , 2010Vilar et al 2010;Magnussen and Taylor 2012;Bedia et al 2014;Karouni et al 2014;Najafabadi et al 2015), low precipitation (Albertson et al 2009;Vasilakos et al 2009;Zhang et al 2010;Plucinski et al 2014;Guo et al 2016a) and low relative humidity (AlonsoBetanzos et al 2003;Padilla and Vega-Garcia 2011;Chang et al 2013;Karouni et al 2014) favour fires and are often used in models. However, fire science has developed methods to estimate the decrease in moisture content caused by weather on litter and fine fuels, medium compact organic layers and deep organic soil layers or heavy fuels for fire danger rating (Dimitrakopoulos et al 2011).…”
Section: Predictors For Short-term Studiesmentioning
confidence: 99%
“…The FWI model is non-dimensional, based on physical processes and has been used at several locations, including the Mediterranean Basin (Viegas et al, 2004;Moriondo et al, 2006, Carvalho et al, 2008Dimitrakopoulos et al, 2011b;Giannakopoulos et al, 2012); indeed, since 2007 the FWI has been adopted at the EU level by the European Forest Fire Information System (EFFIS) of the Joint Research Centre of the European Commission (http://forest.jrc.ec.europa. eu/effis).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have shown that weather and forest Fire Weather Index (FWI) components have significant influence on forest fire (Cortez & Morais, 2007;Carvalho et al, 2008). Cortez and Morais (2007) have concluded in their studies that further research is needed to confirm that direct weather conditions (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, it is well known that weather conditions and fire risks are related, and weather conditions are a crucial factor which determines whether wildfire would occur, and how far it will spread (Wells et al, 2007). A recent statistical survey indicated that weather and forest Fire Weather Index (FWI) components are highly influential in forest fires in Portugal (Carvalho et al, 2008).…”
Section: Introductionmentioning
confidence: 99%